Money and the real world - Davidson, Paul (London: Macmillan, 1972)
This book examines the political economy of modern theory-Keynesians and the Neoclassicist views on money, theory and application in the economy. The author also examines such topics as income distribution, inflation, the relation of incomes policy to monetary and fiscal policy, monetary institutions that make spot markets etc.
Includes bibliographical references.
usc 23/8/17
Loans
Keywords: Money; Finance; Economics